Yoga, Meditation and Mind-Body Health: Increased BDNF, Cortisol Awakening Response, and Altered Inflammatory Marker Expression after a 3-Month Yoga and Meditation Retreat - Cahn, B. Rael; Goodman, Matthew S.; Peterson, Christine T.; Maturi, Raj; Mills, Paul J. (Frontiers in Human Neuroscience, 2017)
Thirty-eight individuals (mean age: 34.8 years old) taking part in a 3-month yoga and meditation retreat were assessed before and after the intervention for psychometric measures, brain derived neurotrophic factor (BDNF) circadian salivary cortisol levels, pro- and anti- inflammatory cytokines. Participation in the retreat was found to be associated with decreases in self-reported anxiety and depression as well as increases in mindfulness. As hypothesized, increases in the plasma levels of BDNF and increases in the magnitude of the cortisol awakening response were also observed. The normalized change in BDNF levels was inversely correlated with BSI-18 anxiety scores at both the pre-retreat (r=0.40, p<0.05) and post-retreat (r=0.52, p<0.005) such that those with greater anxiety scores tended to exhibit smaller pre- to post-retreat increases in plasma BDNF levels. In line with a hypothesized decrease in inflammatory processes resulting from the yoga and meditation practices, we found that the plasma level of the anti-inflammatory cytokine Interleukin-10 was increased and the pro-inflammatory cytokine Interleukin-12 was reduced after the retreat. Contrary to our initial hypotheses, plasma levels of other pro-inflammatory cytokines, including Interferon Gamma (IFN-γ), Tumor Necrosis Factor (TNF-α), Interleukin-1β (IL-1β), Interleukin-6 (IL-6), and Interleukin-8 (IL-8) were increased after the retreat. Given evidence from previous studies of the positive effects of meditative practices on mental fitness, autonomic homeostasis, and inflammatory status, we hypothesize that these findings are related to the meditative practices throughout the retreat; however, some of the observed changes may also be related to other aspects of the retreat such as physical exercise-related components of the yoga practice and diet. We hypothesize that the patterns of change observed here reflect mind-body integration and well-being. The increased BDNF levels observed is a potential mediator between meditative practices and brain health, the increased cortisol awakening response is likely reflection of increased dynamic physiological arousal, and the relationship of the dual enhancement of pro- and anti-inflammatory cytokine changes to healthy immunologic functioning is discussed.